MACRO STRUCTURES IN TWO SOCIAL MEDIA REPORTS ON CAPITAL RELOCATION - Muhammad Fahri Jaya Sudding; Fauzan Hari Sudding; Ashabul Kahfi Susanto; Citra Dwi Safitri; Andi Kamariah (J-Shelves of Indragiri (JSI), 2025)
The relocation of Indonesia’s Capital City has caused public debate and conflicting narratives in media. This research is motivated by the massive coverage of the capital relocation and the assumption that the program is driven by a dominant group with political interests. This research aims to analyze how two online news platforms, such as tirto.id and viva.news, construct discourse on the capital relocation using Van Dijk’s Critical Discourse Analysis model. Employing a qualitative descriptive method, the research focuses on analyzing propositions in selected news texts as well as interpreting their macrostructure through macrorules, such as generalization, deletion, selection, interpretation, and construction. The findings reveal that tirto.id constructs the discourse to support the relocation by highlighting expert involvement and logical reasoning, while viva.news emphasizes political criticism and legal controversies. The research concludes that media framing significantly influences public perception, with each outlet building its own version of reality through discourse strategies along with underlines the role of media in shaping national narratives, especially political issues like capital relocation.